2019
DOI: 10.1038/s41598-019-55046-5
|View full text |Cite
|
Sign up to set email alerts
|

High uptake of Intermittent Preventive Treatment of malaria in pregnancy is associated with improved birth weight among pregnant women in Ghana

Abstract: Despite the clinically proven advantages of intermittent preventive treatment of malaria in pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP), utilisation has been low in many African countries. To increase uptake and achieve the desired effect, the World Health Organization revised the policy to a monthly administration. Assessing the coverage and impact of the revised policy on pregnancy and neonatal outcomes is, therefore, a necessity. A 2-parallel cross-sectional hospital-based study was carried out amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 25 publications
12
31
1
Order By: Relevance
“…Significantly, IPTp-SP 3+ was associated with improved birth weight and reduced the risk of LBW compared to lower doses of SP taken during pregnancy. Similar studies have reported dose-dependent IPTp-SP impact on birth weight [11,30,35]. The effect of malaria on LBW is well known and has been one of the reasons for IPTp-SP use in endemic areas.…”
Section: Discussionsupporting
confidence: 60%
“…Significantly, IPTp-SP 3+ was associated with improved birth weight and reduced the risk of LBW compared to lower doses of SP taken during pregnancy. Similar studies have reported dose-dependent IPTp-SP impact on birth weight [11,30,35]. The effect of malaria on LBW is well known and has been one of the reasons for IPTp-SP use in endemic areas.…”
Section: Discussionsupporting
confidence: 60%
“…We found that more than 3 doses of SP/IPTp signi cantly reduced the odds of LBW. This is in conformity with several studies conducted in Tanzania (41,42), Cameroon (43), Nigeria (44) and Ghana (45). The protective nature of SP against LBW could be explained by its therapeutic effect against both malaria and non-malaria infections.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, all pregnant women residing in areas with high malaria transmission are recommended to receive three or more treatment courses of IPTp with SP, where each course should be administered at least one month apart, starting in the second trimester (67). This replaces the original recommendation of two doses of SP, following substantial data that demonstrated reduced risk of preterm birth and LBW as well as improved birth weight when three or more courses were administered (68)(69)(70). In mathematical modeling studies, it was estimated that three or more doses of IPTp-SP uptake would lead to a 30% relative reduction in LBW occurrence (70)(71)(72)(73).…”
Section: Insecticide-treated Nets Indoor Residual Spraying and Intementioning
confidence: 99%